PENEGAKAN HUKUM TENTANG TINDAK PIDANA KARTU TANDA PENDUDUK GANDA DI KECAMATAN BANGKINANG KOTA BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN - Rika Elvita; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
KTP (Identity Card) is the official identity of the population as proof of self that is issued by the implementing agency and is valid in all regions of the Republic of Indonesia. The dual ID card crime is someone who has a KTP but has more than one KTP printed, besides the KTP he also has another KTP with different data (different NIK). In practice, there are still multiple ID cards in Bangkinang Kota District. The purpose of writing this thesis, namely: first to find out law enforcement efforts against dual ID card crimes by the police in the District of Bangkinang Kota, second to find out the obstacles faced by the police in efforts to enforce the law against dual ID cards in the District of Bangkinang City.This type of research can be classified as sociological, because in this study the authors directly conducted research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in the District Police Station Bangkinang Kota, while the population and sample are all parties related to the problems examined in this study, the source of the data used are primary data, secondary data, and tertiary data, data collection techniques in this study with questionnaires, interview and literature study.From the results of the study it can be concluded that the first 2 things are preventive efforts, in this case the police conducts legal counseling to the community not yet at maximum level, the police's repressive efforts will take action against any community that violates the applicable laws and regulations. The two factors hampering the police are the lack of a service system for making ID cards and the factor of lack of support, knowledge, awareness and community participation.Keywords: Identity Card-Criminal Act-Law Enforcement